2016
DOI: 10.1016/j.prevetmed.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic evaluation of assays for detection of antibodies against porcine epidemic diarrhea virus (PEDV) in pigs exposed to different PEDV strains

Abstract: Porcine epidemic diarrhea virus (PEDV) has caused economic losses in the Americas, Asia and Europe in recent years. Reliable serological assays are essential for epidemiological studies and vaccine evaluation. The objective of this study was to compare the ability of five enzymelinked immunosorbent assays (ELISAs) to detect antibodies against different PEDV strains in pig serum. A total of 732 serum samples from North American or European pigs were tested.Samples included experimental samples from pigs infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…As oppose to large, intense farming holdings, backyard holdings are characterized with lesser people/animal/vehicle circulation, known to be the major biosecurity risk for PEDV entrance and spread [30, 33]. Nevertheless, negative results must be interpreted with caution due to the abovementioned reasons coupled with well-known lower sensitivity of commercially available ELISA kits [34]. Despite the cross-reactivity between PEDV and TGEV that can take place when commercial Ab ELISA tests are used [35, 36], epidemiological evidence of a PEDV outbreak elaborated above [31] strongly suggest that the specificity of the Ab ELISA test used within the study frame was not an issue.…”
Section: Discussionmentioning
confidence: 99%
“…As oppose to large, intense farming holdings, backyard holdings are characterized with lesser people/animal/vehicle circulation, known to be the major biosecurity risk for PEDV entrance and spread [30, 33]. Nevertheless, negative results must be interpreted with caution due to the abovementioned reasons coupled with well-known lower sensitivity of commercially available ELISA kits [34]. Despite the cross-reactivity between PEDV and TGEV that can take place when commercial Ab ELISA tests are used [35, 36], epidemiological evidence of a PEDV outbreak elaborated above [31] strongly suggest that the specificity of the Ab ELISA test used within the study frame was not an issue.…”
Section: Discussionmentioning
confidence: 99%
“…However, we selected that cut-off value (60%) both easily applicable in routine activity and representing the optimal balance of Se (96.5) and Sp (97.69). The sensitivity of the test is therefore very high also in the case of infection due to the more recent PEDV strains belonging to S-INDEL group and it is likely not affected by genetic differences among circulating strains as already observed by Gerber et al (2016) who sustained the capacity of the cELISA to correctly identified pigs infected with G1a, G1b and G2b PEDV.…”
Section: Discussionmentioning
confidence: 78%
“…Additionally, the properties of this PEDV competitive ELISA and its use in field conditions have been analysed. In fact, it has been employed in parallel with a variety of "in-house" and commercial assays set up for the detection of anti-PEDV antibodies in two interlaboratory studies (Gerber et al, 2016;Strandbygaard et al, 2016) to test shared panels of pig sera collected both in the field and during experimental studies in some European and North American countries. As described in these two studies, our "in-house" competitive ELISA "performed very well and exhibited both high Se and Sp" (Se: 97-95% CI 90.0-100.0 Sp: 94-95% CI 83.0-100.0) and "had the overall highest detection" levels (Gerber et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Porcine epidemic diarrhea virus (PEDV) is the causative agent of porcine epidemic diarrhea (PED), a highly contagious enteric disease characterized by severe watery diarrhea, vomiting and dehydration leading to enormous economic losses in the swine industry worldwide [1, 2]. After PEDV was first reported in Belgium in 1971 and the United Kingdom in 1978, it then emerged in other European countries over the following several years [3].…”
Section: Introductionmentioning
confidence: 99%